Cultural Reflections Through Readers’ Responses to Muna Masyari’s Short Stories - Nadifah, Nurul; Roifah, Miftahur (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
This study examines how Muna Masyari’s short stories portray Madurese culture and rituals and how readers from different backgrounds perceive them. It explores cultural representation, reader response variability, and the influence of cultural background. The research collects interview data, analyzes responses, provides cultural insights, and suggests future research to explore evolving perceptions in literature. This qualitative study analyzed readers’ responses to Muna Masyari’s short stories through interviews and observations, focusing on English Literature students from Trunojoyo University. Data analysis included reduction, presentation, and conclusion drawing. Limitations included a small sample size and limited diversity. Future research suggests broader participant diversity, mixed methods, and a diachronic approach to evolving perceptions. The study found that Madurese readers connected deeply with cultural rituals in Muna Masyari’s stories, while non-Madurese readers needed additional context. Responses varied by cultural background, showing pride from locals and fresh perspectives from outsiders. Both groups acknowledged the decline in traditional practices, reflecting changing societal values and the evolving nature of cultural heritage. The study concluded that Muna Masyari’s stories reflect and preserve Madurese culture, showing literature's power to explore identity and challenge stereotypes. Reader response theory revealed how cultural backgrounds shape text interpretation. Future research is expected to involve broader participants and long-term studies to track evolving perceptions. The findings affirm literature's role in bridging cultural gaps and celebrating traditions.